1994
DOI: 10.1128/iai.62.7.2779-2783.1994
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils are critical for host defense against primary infection with the facultative intracellular bacterium Francisella tularensis in mice and participate in defense against reinfection

Abstract: It is generally believed that immunity to experimental infection with the facultative intracellular bacterium FranciseUla tularensis is an example of T-cell-mediated immunity that is expressed by activated macrophages and mediated by Francisella-specific T cells. According to the results presented herein, neutrophils are also essential for defense against primary infection with this organism. It is shown that mice depleted of neutrophils by treatment with the granulocyte-specific monoclonal antibody RB6-8C5 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 19 publications
5
61
0
Order By: Relevance
“…We found that neutropenia induced by treatment with an anti-neutrophil Ab led to a dramatic increase in lethal sensitivity during bacteremia caused by P. aeruginosa, and that neutropenic mice died from smaller amounts of P. aeruginosa than the Cl 2 -MDP-or cyclophosphamide-treated mice. These results demonstrate the key role of neutrophils in protecting against systemic infection with P. aeruginosa or other pathogens, including Legionella pneumophila (20), Listeria monocytogenes (23), Salmonella typhimurium (21), and Francisella tularensis (24). However, neutropenia did not induce differences between the IL-1-deficient and WT mice in susceptibility to P. aeruginosa bacteremia.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We found that neutropenia induced by treatment with an anti-neutrophil Ab led to a dramatic increase in lethal sensitivity during bacteremia caused by P. aeruginosa, and that neutropenic mice died from smaller amounts of P. aeruginosa than the Cl 2 -MDP-or cyclophosphamide-treated mice. These results demonstrate the key role of neutrophils in protecting against systemic infection with P. aeruginosa or other pathogens, including Legionella pneumophila (20), Listeria monocytogenes (23), Salmonella typhimurium (21), and Francisella tularensis (24). However, neutropenia did not induce differences between the IL-1-deficient and WT mice in susceptibility to P. aeruginosa bacteremia.…”
Section: Discussionmentioning
confidence: 70%
“…It has previously been shown that mice with cyclophosphamide-induced bone marrow suppression, which increases their susceptibility to infection, are neutropenic (20)(21)(22)(23)(24). Moreover, Koh et al have generated a gut-derived sepsis model by treating animals with an anti-neutrophil mAb rather than cyclophosphamide (25).…”
Section: Discussionmentioning
confidence: 99%
“…Immune response and apoptosis were well represented (Table 2). Early recruitment of inflammatory cells and production of proinflammatory cytokines (IL18, IL12p40, IFNg) are crucial for innate host defense against systemic LVS infection (Leiby et al, 1992;Sjöstedt et al, 1994;Elkins et al, 2003). These proinflammatory cytokines with increased expression patterns were represented in cluster 1 ( Table 2).…”
Section: Temporal Changes In Gene Expression Induced By F Tularensismentioning
confidence: 99%
“…It is well known that the neutrophil plays an important role in host resistance against different infections (Ferrante et al 1988, Rogers & Unanue 1993, Appelberg et al 1994, Sjöstedt et al 1994. Contrarily, experimental studies in amoebiasis in the hamster have claimed that tissue damage is mediated by lysosomal enzymes released from disintegrated neutrophils and mononuclear cells that accumulate around the amoebae and are killed by this parasite (Tsutsumi et al 1984).…”
Section: Introductionmentioning
confidence: 99%